Flexible Work Arrangements and Employee Outcomes: Evidence from a Systematic Literature Review - Rr. Hawik Ervina; Noni Setyorini; Prianka Nastiti; Heri Prabowo (Universitas 17 Agustus 1945 Semarang, 2026)
Flexible work arrangements (FWAs) have gained increasing attention in contemporary organizations as a strategy to enhance employee-related outcomes in dynamic work environments. This study aims to synthesize empirical evidence on the relationship between flexible work arrangements and employee outcomes through a Systematic Literature Review (SLR) guided by the PRISMA framework. A structured literature search initially identified 200 records, of which 117 peer-reviewed journal articles were retained after excluding non-journal publications. Following full-text screening and eligibility assessment, 45 empirical studies were included in the final analysis. The review reveals that flexible work arrangements are generally associated with positive employee outcomes, particularly job satisfaction, employee well-being, work–life balance, engagement, and performance, although the strength and direction of these relationships vary across organizational contexts and implementation practices. The findings highlight key research trends and methodological gaps, offering valuable insights for future research and practical implications for organizations seeking to effectively implement flexible work arrangements.A